Rehabilitation in Swedish industry an industrial economic analysis - Dahlen, Per.; Wernersson, Stid.
This article presents a framework for calculating the industrial profitability associated with the decision to rehabilitate an employee who is absent due to illness. Practical aspects of the framework are exemplified in a case study from a Swedish engineering company. The case study indicates that the frequent, short-term absence is usually profitable to eliminate through rehabilitation actions.
Keywords: Rehabilitation; Employee absenteeism